Impact of a Forgiveness-Based Intervention on Marital Commitment and Trust Restoration - Chen, Mei-Ling; Sari, Intan (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to evaluate the effectiveness of a forgiveness-based intervention in enhancing marital commitment and restoring trust among married individuals experiencing relational distress.Methods: A randomized controlled trial was conducted with 30 married participants from Indonesia, randomly assigned to either an intervention group (n = 15) or a control group (n = 15). The intervention group received six structured forgiveness-based therapy sessions over six weeks, while the control group received no intervention. Standardized measures of marital commitment and trust were administered at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests, with SPSS version 27.Findings: Results from repeated measures ANOVA revealed significant time × group interaction effects for marital commitment (F(2, 54) = 17.12, p < .001, η² = .39) and trust (F(2, 54) = 19.68, p < .001, η² = .42). Bonferroni post-hoc analyses indicated that both marital commitment and trust significantly increased from pre-test to post-test (p < .001) and were maintained at the five-month follow-up (p < .001), with no significant decline between post-test and follow-up (p > .05).Conclusion: The therapeutic gains were not only immediate but also sustained over time, supporting the use of structured forgiveness interventions in marital counseling settings. These findings highlight the potential of forgiveness as a valuable tool in relationship repair and emotional healing.